Bewegungsfreiheit: Tanz als kulturelle Manifestation (1900-1950) - Rieger, Rita (transcript, 2017)
Dance discourse displays a merging of knowledge of the body and movement, freedom and limitation, aesthetics and politics, and immediacy and mediality.